Long-Term Outcome and Prognostic Factors of Juvenile Dermatomyositis: A Multinational, Multicenter Study of 490 Patients - Ravelli, Angelo; Trail, Lucia; Ferrari, Cristina; Ruperto, Nicolino; Pistorio, Angela; Pilkington, Clarissa; Maillard, Susan; Oliveira, Sheila K.; Sztajnbok, Flavio; Cuttica, Ruben; Beltramelli, Matilde; Corona, Fabrizia; et al. (Wiley-liss, 2010)
Objective. To investigate the long-term outcome and prognostic factors of juvenile dermatomyositis (DM) through a multinational, multicenter study.Methods. Patients consisted of inception cohorts seen between 1980 and 2004 in 27 centers in Europe and Latin America. Predictor variables were sex, continent, ethnicity, onset year, onset age, onset type, onset manifestations, course type, disease duration, and active disease duration. Outcomes were muscle strength/endurance, continued disease activity, cumulative damage, muscle damage, cutaneous damage, calcinosis, lipodystrophy, physical function, and health-related quality of life (HRQOL).Results. A total of 490 patients with a mean disease duration of 7.7 years were included. At the cross-sectional visit, 41.2-52.8% of patients, depending on the instrument used, had reduced muscle strength/endurance, but less than 10% had severe impairment. Persistently active disease was recorded in 41.2-60.5% of the patients, depending on the activity measure used. Sixty-nine percent of the patients had cumulative damage. The frequency of calcinosis and lipodystrophy was 23.6% and 9.7%, respectively. A total of 40.7% of the patients had decreased functional ability, but only 6.5% had major impairment. Only a small fraction had decreased HRQOL. A chronic course, either polycyclic or continuous, consistently predicted a poorer outcome. Mortality rate was 3.1%.Conclusion. This study confirms the marked improvement in functional outcome of juvenile DM when compared with earlier literature. However, many patients had continued disease activity and cumulative damage at followup. A chronic course was the strongest predictor of poor prognosis. These findings highlight the need for treatment strategies that enable a better control of disease activity over time and the reduction of nonreversible damage.